Only hyperuricemia with crystalluria, but not asymptomatic hyperuricemia, drives progression of chronic kidney disease - Sellmayr, Markus; Petzsche, Moritz Roman Hernandez; Ma, Qiuyue; Krüger, Nils; Liapis, Helen; Brink, Andreas; Lenz, Barbara; Angelotti, Maria Lucia; Gnemmi, Viviane; Kuppe, Christoph; Kim, Hyojin; Bindels, Eric Moniqué Johannes; et al. (Journal of the American Society of Nephrology, 2020)
Visual Abstract - Background The roles of asymptomatic hyperuricemia or uric acid (UA) crystals in CKD progression are unknown. Hypotheses to explain links between UA deposition and progression of CKD include that (1) asymptomatic hyperuricemia does not promote CKD progression unless UA crystallizes in the kidney; (2) UA crystal granulomas may form due to pre-existing CKD; and (3) proinflammatory granuloma-related M1-like macrophages may drive UA crystal-induced CKD progression. - Methods MALDI-FTICR mass spectrometry, immunohistochemistry, 3D confocal microscopy, and flow cytometry were used to characterize a novel mouse model of hyperuricemia and chronic UA crystal nephropathy with granulomatous nephritis. Interventional studies probed the role of crystal-induced inflammation and macrophages in the pathology of progressive CKD. - Results Asymptomatic hyperuricemia alone did not cause CKD or drive the progression of aristolochic acid I-induced CKD. Only hyperuricemia with UA crystalluria due to urinary acidification caused tubular obstruction, inflammation, and interstitial fibrosis. UA crystal granulomas surrounded by proinflammatory M1-like macrophages developed late in this process of chronic UA crystal nephropathy and contributed to the progression of pre-existing CKD. Suppressing M1-like macrophages with adenosine attenuated granulomatous nephritis and the progressive decline in GFR. In contrast, inhibiting the JAK/STAT inflammatory pathway with tofacitinib was not renoprotective. - Conclusions Asymptomatic hyperuricemia does not affect CKD progression unless UA crystallizes in the kidney. UA crystal granulomas develop late in chronic UA crystal nephropathy and contribute to CKD progression because UA crystals trigger M1-like macrophage-related interstitial inflammation and fibrosis. Targeting proinflammatory macrophages, but not JAK/STAT signaling, can attenuate granulomatous interstitial nephritis.
Gesehen am 27.01.2021